Urban Cages and Domesticated Humans - Hossein Sadri (Journal of Contemporary Urban Affairs, 2017)
In this article, the study assessed the domestication process of humankind within the frame of urbanization and power accumulation. Within this framework, by giving various examples from chicken farms. The study expresses the author’s opinions on the analogy of the “liberated human beings” in cities and the “free-range” chickens in farms. It has also been tried to explain how a city acts as a human farm. Cities are governed by the ones holding power similar to the farms are ruled by farmers and humans during their history of civilization have lost their right of deciding on their lives and fates against this power as the domesticated animals in farms. It is necessary to give up these cities which are models of life organizations from the Old and the Middle Ages. Models of settlements which became even more inhumane as results of modernization and neo-liberalization strategies. The study revealed that With the scientific and technologic improvements and the developments of in science and humanities, it is possible to easily replace the city model of communal life with a better one -The one in which people can be more free and happy and will give more life to the earth and contribute to the aliveness within it.